Relationships among shoulder rotational strength, range of motion, pitching kinetics, and pitch velocity in collegiate baseball pitchers - Cross, J. A.; Higgins, A. W.; Dziuk, C. C.; Harris, G. F.; Raasch, W. G. (The Journal of Strength and Conditioning Research, 2023)
Throwing shoulder injuries are the most common type of injury experienced by baseball pitchers. Weakness in the shoulder musculature and insufficient throwing arm range of motion are both risk factors for developing a shoulder injury. The goal of this study was to determine correlations among shoulder rotational strength, range of motion, pitching kinetics, and pitch velocity in collegiate pitchers. Thirteen uninjured male college pitchers were evaluated. Clinical measures included shoulder internal and external rotation range of motion, peak isokinetic internal and external rotator strength, and peak isometric internal and external rotator strength. Three-dimensional biomechanics were assessed as subjects threw from an indoor pitching mound to a strike zone net at regulation distance. Pearson's correlations were used to assess the associations among the clinical measures and throwing metrics. Five significant correlations were found between peak shoulder compressive force and strength, and 4 significant correlations were found between pitching velocity and strength (p < 0.05). No significant correlations were found between range of motion and pitching kinetics or velocity. Our results suggest that as shoulder rotational strength increases, the peak shoulder compressive force and pitch velocity both increase. Knowledge of relationships between strength metrics and pitching biomechanics may allow for improved strength training routines with the goal of increasing velocity without increasing injury risk.